Health promotion education in changing and challenging times: Reflections from England. (October 2019) - Warwick-Booth, Louise; Cross, Ruth; Woodall, James; Bagnall, Anne-Marie; South, Jane
Health education has changed in many ways since Health Education Journal was first published, with developments moving the discipline forward in ways not envisaged 75 years ago. While there have been recent concerns about the decline in status of health promotion and linked worries about health education, the contemporary evidence base has grown to support the delivery of good quality health education and the development of capable and skilled practitioners. Pedagogy has further developed as well, and new technology now enables health education to have broader reach through online teaching and learning, social media and open-access publications. Global challenges remain, however, and the context in England is one in which both education and practice face major trials despite the contribution that health education has made by those educated and trained in this setting over a period of many years.